Breast Cancer Presents With a Paraneoplastic Neurologic Syndrome - Coelho Barata, P (2012)
BACKGROUND: Paraneoplastic neurologic syndromes (PNS) pose quite an uncommon neurological complication, affecting less than 1% of patients with breast cancer. Nearly one third of these patients lack detectable onconeural antibodies (ONAs), and improvement in neurologic deficits with concomitant cancer treatments is achieved in less than 30% of cases. CASE PRESENTATION: A 42-year-old, premenopausal woman presented with facial paralysis on the central left side accompanied by a left tongue deviation, an upward vertical nystagmus, moderate spastic paraparesis, dystonic posturing of the left foot, lower limb hyperreflexia and bilateral extensor plantar reflex. After ruling out all other potential neurologic causes, PNS was suspected but no ONAs were found. A PET-CT scan detected increased metabolism in the right breast, as well as an ipsilateral thoracic interpectoral adenopathy. Core biopsy confirmed the presence of an infiltrating duct carcinoma. After breast surgery, the neurologic symptoms disappeared. One week later, the patient was readmitted to the hospital with a bilateral fatigable eyelid ptosis, and two weeks later, there was a noticeable improvement in eyelid ptosis, accompanied by a rapid and progressive development of lower spastic paraparesis. She started adjuvant treatment with chemotherapy with marked clinical and neurological improvement, and by the end of radiotherapy, there were no signs of neurologic impairment. CONCLUSION: This case study highlights the importance of a high level of vigilance for the detection of PNS, even when ONAs are not detected, as the rapid identification and treatment of the underlying tumor offers the best chance for a full recovery.